Effect of grazing on main elements C, N, and P content in nutrition cycle of plant and soil in the meadow - Batzaya, Gachmaa; Azzaya, Jukov; Tumenjargal, Tsogtsaikhan; Tuvshintogtokh, Indree; Enkhriimaa, Narmandakh (Mongolian Journal of Botany, 2022)
We conducted this analysis using the long-term vegetation monitoring field in the Laboratory of Plant Vegetation and Plant Economics of Botanical Garden and Research Institute. This study aimed to evaluate the effect of grazing on C, N, P, moisture content, the difference between plant species, and soil depth. The soil and plant samples used in the study were prepared according to the updated methodology (2019) on the topic “Effects of grazing on some factors of steppe ecosystem services” and laboratory analysis was conducted. The carbon (C), phosphorus (P), and moisture content of the 7 dominant plant species in the fenced field were high, whereas the N-nitrogen content was high in the unfenced field. Furthermore, the difference between the fenced and unfenced plant species was very high (p 0.05). The soil moisture content of the fenced field and the content of carbon (C), nitrogen (N), and phosphorus (P) in the soil of the unfenced field were high, respectively. The content of C-carbon, N-nitrogen, P-phosphorus, and moisture were the highest in the depth of 0-10 cm of the fenced and unfenced field. There was no difference between the depth of 10-30 cm and 30-50 cm. The content of C-carbon, N-nitrogen, P-phosphorus, and moisture varies significantly depending on soil depth (p 0.05). As a result, grazing has a definite effect on the carbon (C), nitrogen (N), phosphorus (P), and moisture content of soil and plants. The plant’s C-carbon content (0.1-0.3%), P-phosphorus content (0.1-0.4%), moisture content (0.1-0.2%) decreased, and N-nitrogen content (0.1-0.6%) increased. In the case of soils, the phosphorus content increased (0.4-0.8 mg/kg) and no changes were observed in the other variables numerically (p> 0.05). This study found that grazing has a stronger effect on plant C-carbon and N-nitrogen content than soil. Татмын нугын хөрс болон ургамлын тэжээлийн эргэлтэд гол үүрэг гүйцэтгэгч зарим элементийн (C, N, P) агууламжид мал бэлчээрлэлтийн нөлөө Хураангуй. Бид Ботаникийн цэцэрлэгт хүрээлэнгийн Ургамалжлын экологи, ургамлын эдийн засгийн лабораторийн ургамалжлын урт хугацааны мониторингийн суурин судалгааны төв болох Төв аймгийн Мөнгөнморьт сумын Баруун бүрхийн аманд орших татмын нугын Үетэн- алаг өвст бүлгэмдлийн хөрс болон ургамлын нүүрстөрөгч (C), азот (N), фосфор (P), чийгийн агууламжид мал бэлчээрлэлтийн нөлөөг илрүүлэх, ургамлын зүйл, хөрсний гүн хоорондын ялгааг тогтоох зорилготой энэхүү судалгааг явуулсан. Судалгаанд ашиглагдсан хөрс болон ургамлын дээжийг “Хээрийн экосистемийн үйлчилгээний зарим үзүүлэлтүүдэд бэлчээр ашиглалтын үзүүлэх нөлөө” сэдэвт ажлын шинэчилсэн арга зүй (2019)-н дагуу бэлтгэж, лабораторийн туршилтыг явуулсан. Судалгааны үр дүнд хашсан талбайн зонхилогч 7 зүйл ургамлын С, P, чийгийн агууламж өндөр, хашаагүй талбайн N-ын агууламж өндөр байсан ба хашсан, хашаагүй талбайн ургамлын зүйл хоорондын ялгаа маш өндөр байсан (p<0.05). Харин хашсан талбайн хөрсөн дэх чийгийн агууламж мөн хашаагүй талбайн харсөн дэх С, N, P-ын агууламж тус тус өндөр байсан бөгөөд хашсан, хашаагүй талбайн хөрсний 0-10 см гүнд С, N, P, чийгийн агууламж хамгийн их, 10-30 см, 30-50 см –ын гүн хооронд ялгаа ажиглагдаагүй. Хөрсний гүнээс хамаарч С, N, P, чийгийн агууламж нь эрс ялгаатай байна (p<0.05). Үүнээс дүгнэхэд мал бэлчээрлэлт нь тухайн ургамал бүлгэмдлийн ургамал болон хөрсний С, N, P, чийгийн агууламжид тодорхой хэмжээнд нөлөөлж байна. Ингэхдээ ургамлын С (0.1-0.3%), P (0.1-0.4%), чийгийн агууламж (0.1- 0.2%) буурч, N- ын агууламж (0.1-0.6%) нэмэгдэх байдлаар илэрч байв. Харин хөрсний хувьд фосфорын агууламж (0.4-0.8 мг/кг) нэмэгдэж, бусад үзүүлэлтүүдэд өөрчлөлт илэрсэнгүй. Эндээс мал бэлчээрлэлт нь ургамлын С- нүүрстөрөгч, N- азот агууламжид хөрснөөс илүү хүчтэй нөлөөлж байгааг энэхүү судалгаагаар тогтоов. Түлхүүр үгс: С- нүүрстөрөгч, N- азот, P-фосфор, татмын нуга, хөрс, ургамал